Femtomolar detection of silver nanoparticles by flow-enhanced direct-impact voltammetry at a microelectrode array - Sokolov, S; Bartlett, T; Fair, P; Fletcher, S; Compton, R (American Chemical Society, 2016)
We report the femtomolar detection of silver (Ag) nanoparticles by direct-impact voltammetry. This is achieved through the use of a random array of microelectrodes (RAM) integrated into a purpose-built flow cell, allowing combined diffusion and convection to the electrode surface. A coupled RAM-flow cell system is implemented and is shown to give reproducible wall-jet type flow characteristics, using potassium ferrocyanide as a molecular redox species. The calibrated flow system is then used to detect and quantitatively size Ag nanoparticles at femtomolar concentrations. Under flow conditions, it is found the nanoparticle impact frequency increases linearly with the volumetric flow rate. The resulting limit of detection is more than 2 orders of magnitude smaller than the previous detection limit for direct-impact voltammetry (900 fM) [J. Ellison et al. Sens. Actuators, B 2014, 200, 47], and is more than 30 times smaller than the previous detection limit for mediated-impact voltammetry (83 fM) [T. M. Alligrant et al. Langmuir 2014, 30, 13462].